0320 Indirect parent-mediated pathways of child exposure to 2, 4-d and chlorpyrifos in farm families. (21st August 2017) - Hernandez, Ashley; Church, Timothy; Mandel, Jack; Alexander, Bruce
Abstract : Background: To reduce children's exposure to pesticides used on farms, identifying and interrupting exposure pathways is critical. We evaluated applicator (parent) exposure as a determinant of children's paraoccupational exposure to chlorpyrifos or 2, 4- Dichlorophenoxyacetic Acid (2, 4-D) in a study of farm families who used one of these pesticides as part of their usual practice. Methods: The sample included 34 applicators applying 2, 4-D (n=53 children) or chlorpyrifos (n=50 children). Sequential 24 hour urine samples were collected on the day preceding application through the third day after application of chlorpyrifos or 2, 4-D. Maximum post-application urine concentrations of 3, 5, 6-trichloropyridinol (TCP), a chlorpyrifos metabolite, and 2, 4-D (log-transformed) were used to examine the association of children's exposure with applicator exposure using mixed model regression including a random intercept for farm to account for correlation. The final adjusted model included children's age, gender, and presence during the application as covariates. Separate models were fit based on children's presence or absence during the application. Results: Adjusted models revealed positive associations between children's exposure with applicators' exposure (TCP: β=0.257; 95% CI=0.052, 0.462; 2, 4-D: β=0.593, 95% CI=0.364, 0.822). The association persisted among children who were absent during the application process (TCP: β=0.218, 95% CI=−0.029, 0.466; 2, 4-D: β=0.547, 95% CI=0.283, 0.811). Conclusions: Specific pesticide exposure pathways to children living on farms are difficult to identify, but these data indicate that applicator exposure is associated with exposures to their children absent any known direct exposure to the children. Applicators protecting themselves from exposures may also protect their children.